A Unifying Vision: Shingwaukonse’s Plan for the Future of the Great Lakes Ojibwa - Chute, Janet (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1996)
AbstractThe speeches of Shingwaukonse between 1846 and 1850 furnish some of the most explicit testimonials to the principle of Native right to be expressed in the United Canadas during the mid-nineteenth century. Shingwaukonse's ideas and actions set precedents which exerted a profound influence on the future course of Indian policy in Canada. By 1850, the chief had defined three major goals for Ojibwa people: first, to establish linkages with government agencies just beginning to exercise jurisdiction in the Upper Great Lakes area; second, to preserve an environment in which Native cultural values and organisational structures could survive; and finally, to devise new strategies conducive to the formation of band governments capable of assuming a degree of proprietorship over resources on Indian lands. Recently a debate has arisen in Canadian historiography over what constitutes “Native agency“, as distinct from “Native viclimhood”. This paper not only rejects the idea that “victimhood“ describes the fate of Shingwaukonse's leadership career, but also stresses the need for the concept of “Native agency” to be expanded beyond the semantic parameters set by the agent/victim dichotomy, so that it may prove a better analytical tool to examine historic evidence of this chief's ideas and actions obtained from both oral and documentary sources.